Effects on human body and conductive body over a near field communication antenna. Issue 9 (13th June 2021) - Benavides, M.; Miralles, D.; Andújar, A.; Anguera, J.
ABSTRACT: The paper presents an NFC antenna based on a rectangular spiral examining the effect of the geometry and the addition of a ferrite sheet. Several prototypes are fabricated and tested where the influence of a human wrist and a conducting body close to the antenna are studied.